EXPERIMENTAL DETERMINATION OF OXYGEN ISOTOPE FRACTIONATIONS BETWEEN CO2 VAPOR AND SODA-MELILITE MELT - Appora I.; Eiler J.M.; Matthews A.; Stolper E.M. (My University, 2003)
We report results of experiments constraining oxygen isotope fractionations between CO2 vapor and Na-rich melilitic melt at 1 bar and 1250 and 1400°C. The fractionation factor constrained by bracketed experiments, 1000.lnαCO2-Na melilitic melt, is 2.65+/-0.25 %% (+/-2σ; n=92) at 1250°C and 2.16+/-0.16 %% (2σ; n=16) at 1400°C. These values are independent of Na content over the range investigated (7.5 to 13.0 wt. % Na2O). We combine these data with the known reduced partition function ratio of CO2 to obtain an equation describing the reduced partition function ratio of Na-rich melilite melt as a function of temperature. We also fit previously measured CO2-melt or -glass fractionations to obtain temperature-dependent reduced partition function ratios for all experimentally studied melts and glasses (including silica, rhyolite, albite, anorthite, Na-rich melilite, and basalt). The systematics of these data suggest that reduced partition function ratios of silicate melts can be approximated either by using the Garlick index (a measure of the polymerization of the melt) or by describing melts as mixtures of normative minerals or equivalent melt compositions. These systematics suggest oxygen isotope fractionation between basalt and olivine at 1300°C of approximately 0.4 to 0.5%%, consistent with most (but not all) basalt glass-olivine fractionations measured in terrestrial and lunar basalts.